Dirac dispersions, lattice dynamics and thermoelectric properties of quaternary Heusler alloys LiMgXY(X = Pt, Pd, Au; Y= Sb, Sn). (June 2022) - Nag, Abhinav; Kumar, Jagdish
Abstract: This manuscript reports the structural, mechanical, electronic, and thermoelectric properties of the LiMgYZ system Y = t, Pd, Au; Z = Sb, Sn) computed within the first-principle density functional theory combined with semi-classical Boltzmann transport equations. Comparing the relative energetic stability of type-I, type-II, and type-III atomic arrangement of basis atoms, the type-I arrangement is found to be the most stable among these. The lattice dynamics also confirm that the type-I phase is stable for all the studied alloys except LiMgAuSn. It is interesting to note that the electronic band structure of these materials exhibits the Dirac point. The temperature-dependent transport coefficients of these materials have been calculated within semi-classical Boltzmann transport formalism within constant scattering time approximation (CSTA). The number of states at the Fermi level has successfully depicted the behavior of electrical conductivity. Among all the studied alloys, LiMgPtSb shows the highest temperature coefficient of resistivity which indicates that this material can be a good candidate for temperature sensing applications. Graphical Abstract: ga1